Pengaruh Pemanfaatan Multimedia Interaktif terhadap Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam Sekolah Dasar - Unik Hanifah Salsabila; Nafiatun Nihayah; Muhammad Zakaria Abdullah; Hendra Kusuma Pratama (Jurnal Ilmiah Jendela Pendidikan, 2022)
evelopment of technology and media science today causes the development of the world of education and one of them is the development of learning media. Learning media is an important factor that supports success in a learning. One of the learning media that is growing rapidly is software or software-based media. The concept of media in the field of education is to develop motivational aspects, especially for elementary school children where the thinking aspects in their thinking still use the concept of playing while learning. This makes a teacher have to provide a tool or medium in increasing motivation, especially in teaching children in the school. One of the subjects that must be focused on is the subject of Islamic religious education, where this Islamic religious education subject requires the patience of teachers in teaching their students. Because of this, a teacher needs to provide enough motivation so that his students want to participate in the learning process. So, the existence of a media can help facilitate with the concept of interactive media. Through the use of this interactive media, students become more excited and want to learn more about aspects of Islamic religious education. Meanwhile, on the other hand, the students also have a more rational thinking aspect because they are able to take part in this interactive media-based learning. Where this interactive media covers the subject area of Islamic religious education